Injuries and Concussions in Female High School Rugby: Prevention is Worth a Try. Issue 5 (10th September 2022) - Shill, Isla J.; West, Stephen W.; Sick, Stacy; Schneider, Kathryn; Hagel, Brent E.; Pasanen, Kati; Wiley, James Preston; Emery, Carolyn A.; Black, Amanda M.
Abstract : Objectives: To describe injury and concussion rates and mechanisms in female high school rugby players. Design: Two-year prospective cohort study. Setting: High school rugby. Participants: Participants included 214 female High school rugby players (year 1) and 207 female High school players (year 2) from the Calgary Senior High School Athletics Association 2018 and 2019 rugby competition. Intervention: None. Main Outcome Measures: Match and training injury and concussion. Injury definition included any injury resulting in time loss, inability to complete a session, and/or requiring medical attention. Details of reported injuries were collected on injury report forms and validated by a certified athletic therapist on a validated online injury surveillance platform. Exposure hours for players were tracked using paper or virtual weekly exposure forms by team designates. Results: A match incidence rate (IR) = 93.7 injuries/1000 match hours (95% confidence intervals (CI): 78.6-11.7) and training IR = 5.3 injuries/1000 training hours (95% CI: 4.0-6.9) were estimated. The tackle accounted for 109 (70%) match and 37 (44%) training injuries. Tackling was the most frequent mechanism of injury (IR = 37.5 injuries/1000 match hours, 95% CI: 27.5-51.8 and 1.2 injuries/1000 training hours, 95% CI: 0.7-2.4). Sixty-two match concussions (IR = 37.5 concussions/1000 match hours, 95% CI: 26.8-52.3) and 16 training concussions (IR = 1.0 concussions/1000 training hours, 95% CI: 0.7-1.4) occurred. Of 78 reported concussions, 78% for match and 56% for training were physician diagnosed. Tackling was the most frequent mechanism of concussion in matches (IR = 18.1 concussions/1000 match hours, 95% CI:11.4-28.6). Conclusions: Injury and concussion rates in female high school rugby are high. The tackle accounted for the highest proportion of injuries. Prevention strategies (eg, tackle policy change, tackle-training programs, and neuromuscular training) should be explored to increase sport safety.